Crystallization and Melting Behavior of UHMWPE Composites Filled by Different Carbon Materials - Anqi Li; Fuzhen Li; Kancheng Mai; Zishou Zhang (Advances in Polymer Technology)
In order to understand the effect of different carbon materials on the crystallization and melting behavior of ultrahigh molecular weight polyethylene (UHMWPE), UHMWPE composites were prepared by different carbon materials through solution mixing in this paper. UHMWPE was oxidized to improve the interfacial interaction between UHMWPE and carbon materials. The UHMWPE composites and oxidized UHMWPE composites were prepared using granular graphite particle (GP), graphite nanoplatelets (GNP), and flaky graphene oxide (GO) as fillers. The effect of the type and the content of carbon materials and the oxidization of UHMWPE on crystallization and melting temperatures, crystallinity, and crystal form of UHMWPE and oxidized UHMWPE composites was investigated by differential scanning calorimetry, X-ray diffraction, scanning electron microscope, X-ray photoelectron spectrum, and Fourier transform infrared spectroscopy. The results indicated that there are coexistence of the heterogeneous nucleation and the hindering effect of crystal growth by carbon materials for UHMWPE crystallization. The different influence of carbon materials on the crystallization and melting behavior of UHMWPE was discussed by the heterogeneous nucleation of carbon materials and the restriction of the macromolecular chain motion of UHMWPE by carbon materials.